Characterizing metabolic drivers of Clostridioides difficile infection with activity-based hydrazine probes - Bustin, Katelyn A.; Abbas, Arwa; Wang, Xie; Abt, Michael C.; Zackular, Joseph P.; Matthews, Megan L. (Frontiers in Pharmacology, 2023)
Many enzymes require post-translational modifications or cofactor machinery for primary function. As these catalytically essential moieties are highly regulated, they act as dual sensors and chemical handles for context-dependent metabolic activity. Clostridioides difficile is a major nosocomial pathogen that infects the colon. Energy generating metabolism, particularly through amino acid Stickland fermentation, is central to colonization and persistence of this pathogen during infection. Here using activity-based protein profiling (ABPP), we revealed Stickland enzyme activity is a biomarker for C. difficile infection (CDI) and annotated two such cofactor-dependent Stickland reductases. We structurally characterized the cysteine-derived pyruvoyl cofactors of D-proline and glycine reductase in C. difficile cultures and showed through cofactor monitoring that their activity is regulated by their respective amino acid substrates. Proline reductase was consistently active in toxigenic C. difficile, confirming the enzyme to be a major metabolic driver of CDI. Further, activity-based hydrazine probes were shown to be active site directed inhibitors of proline reductase. As such, this enzyme activity, via its druggable cofactor modality, is a promising therapeutic target that could allow for the repopulation of bacteria that compete with C. difficile for proline and therefore restore colonization resistance against C. difficile in the gut.